Potential therapeutic targets of Klebsiella pneumoniae : a multi-omics review perspective - Ali, Sabeeha; Alam, Manzar; Hasan, Gulam Mustafa; Hassan, Md Imtaiyaz (Briefings in functional genomics, 2022)
The multidrug resistance developed in many organisms due to the prolonged use of antibiotics has been an increasing global health crisis. Klebsiella pneumoniae is a causal organism for various infections, including respiratory, urinary tract and biliary diseases. Initially, immunocompromised individuals are primarily affected by K. pneumoniae. Due to the emergence of hypervirulent strains recently, both healthy and immunocompetent individuals are equally susceptible to K. pneumoniae infections. The infections caused by multidrug-resistant and hypervirulent K. pneumoniae strains are complicated to treat, illustrating an urgent need to develop novel and more practical approaches to combat the pathogen. We focused on the previously performed high-throughput analyses by other groups to discover several novel enzymes that may be considered attractive drug targets of K. pneumoniae. These targets qualify most of the selection criteria for drug targeting, including an absence of its homolog’s gene in the host. The capsule, lipopolysaccharide, fimbriae, siderophores and essential virulence factors facilitate the pathogen entry, infection and survival inside the host. This review discusses K. pneumoniae pathophysiology, including its virulence determinants and further the potential drug targets that might facilitate the discovery of novel drugs and effective treatment regimens shortly.